2022
DOI: 10.3389/fpubh.2022.1018460
|View full text |Cite
|
Sign up to set email alerts
|

Association between sedentary behavior, physical activity, and cardiovascular disease-related outcomes in adults—A meta-analysis and systematic review

Abstract: BackgroundSedentary behavior (SB) and physical activity (PA) are modifiable risk factors for cardiovascular disease (CVD); however, previous research on the effects of PA and SB on CVD has been relatively homogeneous. Our study investigated the association between PA, SB, and CVD-related outcomes.MethodsA comprehensive search strategy was conducted in the MEDLINE, Embase, Cochrane Library, and Web of Science databases from their inception to September 2022. We identified eligible studies according to PICOS: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…56 This was supported by another systematic review and meta-analysis of 148 RCTs and 36 longitudinal studies that found that PA reduced the risk of CVD and sedentary behavior raised the risk of CVD. 57…”
Section: Prevalence and Secular Trendsmentioning
confidence: 99%
“…56 This was supported by another systematic review and meta-analysis of 148 RCTs and 36 longitudinal studies that found that PA reduced the risk of CVD and sedentary behavior raised the risk of CVD. 57…”
Section: Prevalence and Secular Trendsmentioning
confidence: 99%
“…Adults spent a mean of 8.2 hours per day (range 4.9–11.9 h/day) in SB during waking hours (i.e., excluding the sleep period) [ 2 , 3 ]. Extended periods of time spent in SB activities have been associated with the development of cardiovascular diseases, diabetes type 2, and a high risk of mortality [ 4 , 5 ]. The mortality rate is increased by 2% for each hour sitting and increased further (almost 8%) if the sitting time is more than 8 h a day [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific research has investigated the relationship between unhealthy lifestyle behaviors and the risk of cardiovascular events [ 34 , 35 ]. Referring to a meta-analysis, one study determined that long-term sedentary behavior and physical inactivity increased the risk of cardiovascular diseases (CVD) in healthy adults [ 34 ]. In addition, another study provided evidence concerning health promoting behaviors (HPB) and risk of cardiovascular events among patients with CVD.…”
Section: Discussionmentioning
confidence: 99%